IMPLEMENTASI PENILAIAN AUTENTIK DALAM KURIKULUM 2013 PADA PEMBELAJARAN BAHASA INDONESIA (STUDI KASUS DI SMA NEGERI 1 GEMOLONG) - Agita Dio Divanda; Sarwiji Suwandi; Sri Hastuti (Universitas Sebelas Maret, 2018)
This research is a case study research aims. Data sources include events, informants, and documents. Research subjects are Indonesian language teachers, Vice Principals of Curriculum, andstudents of SMA N 1 Gemolong. Technique of research subject taken by purposive sampling technique. Technique of data collecting done by observation, interview, and document analysis. The technique of data validity test is done by triangulation of source and triangulation method. Data analysis techniques use interactive analysis techniques.The results of this study are descriptions of: (1) the planning of authentic assessment in the Curriculum 2013 in Indonesian learning includes the preparation of assessment indicators, assessment criteria, and rubrics on RPP; (2) the implementation of authentic assessment in the Curriculum 2013 on learning Indonesian, teachers carry out authentic assessment in learning; (3) obstacles that teachers encounter in the conduct of authentic assessment and efforts to overcome them. Obstacles encountered by teachers include: (1) time constraints; (2) the difficulty of applying authentic assessment of certain competencies (3) the complexity of authentic assessment of (4) age. Efforts to overcome authentic assessment constraints include: (1) teachers make arrangements that include agreement between teachers and learners to perform assessments at specific times and places; (2) the teacher considers the assessments obtained from various sources; (3) teachers attend various trainings that are authentic assessment concepts; (4) the school provides an application to determine the value of the learner.